Urban Farming: Program Pemanfaatan Lingkungan Untuk Pengembangan Pertanian Perkotaan di Kota Semarang - Rahmad Aji Maulana; Hardi Warsono; Retno Sunu Astuti; Teuku Afrizal (Universitas Medan Area, 2022)
Urban population growth accompanied by the phenomenon of urbanization is a global issue. This raises challenges and problems in various aspects, including the decline in environmental quality due to reduced agricultural land/green spaces that are changing functions and the need for adequate food availability. As has been implemented in various cities in the world, urban farming activities were then developed as a promising solution to supply sustainable quality agricultural products. Following up on this, this study aims to develop urban agriculture (urban farming) in the city of Semarang to increase community productivity and co-benefits. The analysis carried out includes a qualitative descriptive analysis supported by secondary and primary data. There are 2 (two) indicators of the results and discussion of this research, namely (a) the development of urban agriculture (urban farming) in the city of Semarang, and (b) the benefits of urban agriculture (urban farming) in the city of Semarang. The potential for urban agriculture in the city of Semarang is very diverse, including various types of vegetables, cassava, sugar cane, durian, and mushrooms. In addition, various other benefits of urban agriculture, namely environmental, economic, social, health, education and tourism benefits are added values ​​that are very important to encourage the development of this activity in a more massive and structured manner. Policy instruments through appropriate top-down and bottom-up approaches are essential.